2009
DOI: 10.1063/1.3266909
|View full text |Cite
|
Sign up to set email alerts
|

Resonance excitation of single rotons in He II by an electromagnetic wave. Spectral line shape

Abstract: The amplitude-frequency characteristic of the spectral line of electromagnetic absorption in liquid helium is measured in the frequency range 40–200GHz at temperatures in the interval 1.4–2.75K. It is found that in the roton frequency region a narrow resonance absorption line on a broad pedestal is observed. The results are compared with data on the roton spectrum found in neutron scattering experiments in liquid helium. The narrow line is due to the creation of a single roton. It is shown that the momentum co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 15 publications
2
21
0
1
Order By: Relevance
“…29), D % 8.4 K. These values are indeed close to the value of the temperature-dependent roton energy. 9 Due to the significant difference between the experiments on the absorption of electromagnetic field and slow neutron scattering, direct detection of the gapped branch of the spectrum in the neutron experiments is apparently impossible. This is due to several reasons.…”
Section: Possibility Of Resonant Absorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…29), D % 8.4 K. These values are indeed close to the value of the temperature-dependent roton energy. 9 Due to the significant difference between the experiments on the absorption of electromagnetic field and slow neutron scattering, direct detection of the gapped branch of the spectrum in the neutron experiments is apparently impossible. This is due to several reasons.…”
Section: Possibility Of Resonant Absorptionmentioning
confidence: 99%
“…2,3 Unexpectedly high electric activity of superfluid helium exhibited under different conditions has been reported in a series of experimental studies. [4][5][6][7][8][9][10] In particular, the absorption of electromagnetic radiation at a frequency close to the roton energy has been observed. Moreover, the observed absorption was anomalously narrow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their experimental investigation of the interac tion of microwaves with superfluid 4 He, Rybalko et al [1] observed resonance absorption at the roton fre quency f 0 ~ 180 GHz. Since the momentum of a pho ton is much lower than that of a roton, their transfor mation into one another is possible only near the wall, where only the energy is conserved.…”
mentioning
confidence: 99%
“…Rybalko et al [1] used "whispering gallery" modes disk dielectric resonator with the radius R ~ 1 cm immersed in liquid helium. The electric field in helium obeys the harmonic law E(t) = Ecos2πft.…”
mentioning
confidence: 99%